Evidence for surface defect passivation as the origin of the remarkable photostability of unencapsulated perovskite solar cells employing aminovaleric acid as a processing additive. Issue 7 (29th January 2019) - Lin, Chieh-Ting; De Rossi, Francesca; Kim, Jinhyun; Baker, Jenny; Ngiam, Jonathan; Xu, Bob; Pont, Sebastian; Aristidou, Nicholas; Haque, Saif A.; Watson, Trystan; McLachlan, Martyn A.; Durrant, James R.
Abstract : AVA can passivate surface defect sites, resulting in enhanced resistivity to oxygen/light induced degradation. Abstract : This study addresses the cause of enhanced stability of methyl ammonium lead iodide when processed with aminovaleric acid additives (AVA-MAPbI3 ) in screen printed, hole transport layer free perovskite solar cells with carbon top electrodes (c-PSC). Employing AVA as an additive in the active layer caused a 40-fold increase in device lifetime measured under full sun illumination in ambient air (RH ∼ 15%). This stability improvement with AVA was also observed in optical photobleaching studies of planar films on glass, indicating this improvement is intrinsic to the perovskite film. Employing low-energy ion scattering spectroscopy, photoluminescence studies as a function of AVA and oxygen exposure, and a molecular probe for superoxide generation, we conclude that even though superoxide is generated in both AVA-MAPbI3 and MAPbI3 films, AVA located at grain boundaries is able to passivate surface defect sites, resulting in enhanced resistivity to oxygen induced degradation. These results are discussed in terms of their implications for the design of environmentally stable perovskite solar cells.